DAMPAK SOSIAL EKONOMI MASYARAKAT TERHADAP KEPADATAN PENDUDUK DI KENAGARIAN IV KOTO PULAU PUNJUNG KECAMATAN PULAU PUNJUNG KABUPATEN DHARMASRAYA - Ance, Febry; Juita, S.Pd. M.Si, Erna; Prari Keslan, Widya (STKIP PGRI Sumbar, 2014)
ABSTRACT This research aims to determine the impact of socio-economic community to population density in the Kenagarian IV Koto Pulau Punjung Kecamatan Pulau Punjung Kabupaten Dharmasraya. This research is a descriptive correlation. Samples were taken proportional Random Sampling technique with a proportion of 10% for the sample region with a population of 1.627 households, so that the sample of respondents quantity 163 households. The results of the research found that : 1. There is a relationship of fertility to population density, because of thitung>ttable (3.351>1.974), the low strength of the relationship (r=0.255) and a very small contribution (6.5 %), 2. There was no relationship of access infrastructure to population density, because of t hitung>ttable (0.750<1.974), including a very low strength of the relationship (r=0.059) and a very small contribution (0.3%), 3.There is a relationship of education to population density, because of thitung>ttable (4.253>1.974), the low strength of the relationship (r=0.318) and a small contribution (10.1%) and 4. There is a relationship fertility, access to infrastructure and education on population density because of Fhitung> Ftable (7.595>2.67), the strength of these three variables to variable Y low (r=0.354) and a small contribution (12,5%) were the dominant fertility.